Spatial distribution and interference of wave impact loads among structural components of a semi-submersible. (15th September 2020) - Guo, Yinghao; Xiao, Longfei; Lu, Wenyue; Wei, Handi; Li, Lei; Deng, Yanfei
Abstract: Recent accidents caused by wave impact loads have attracted increasing concerns from academia and industry. An experimental study was carried out to investigate the local wave impact loads on a semi-submersible exposed to various sea states, focusing on the spatial distributions and interference among the fore column, aft column, deck bottom and deck side. A versatile tool based on the conditional probability is proposed and used along with correlation analyses to evaluate the interference among different components. The results show that the wave impact loads on the semi-submersible are of high nonlinearity and the aft column is the worst-hit component where wave impacts occur most frequently. The transition region between the fore column and deck side is the most dangerous area for extremely large waves, while the connection corner deserves particular concerns for the aft column and the deck bottom. The horizontal variation of wave impact loads is not significant on the fore column, but is remarkable within the width of the deck side. The interference examination reveals that wave impact loads on different components are correlated at varying levels under different wave impact scenarios. The in-depth analysis improves the understanding of wave impact events on multi-column floating structures. Highlights: Conducted a systematic experimental study on the local wave impact loads on a semi-submersible under various sea states. Demonstrated the nonlinear characteristics of wave impact loads. The spatial distributions of wave impact loads on different structural components were investigated. Proposed a versatile tool based on the conditional probability to evaluate the interference of wave impact loads among different components.